Monkeypox, a Literature Review: What Is New and Where Does This concerning Virus Come From? - Giorgio Tiecco; Melania Degli Antoni; Samuele Storti; Lina Rachele Tomasoni; Francesco Castelli; Eugenia Quiros-Roldan (Viruses, 2022)
Among the Poxviridae family, orthopoxvirus is the most notorious genus. Several DNA viruses belonging to this group are known to produce human disease from the life-threatening variola virus (VARV) (the causative agent of smallpox), monkeypox virus (MPXV), cowpox virus (CPXV), and vaccinia virus (VACV). These orthopoxviruses still remain a public health concern as VACV or CPXV still cause emerging endemic threads, especially in developing countries. MPXV is able to cause sporadic human outbreaks of a smallpox-like zoonotic disease and, in May 2022, hundreds of cases related to MPXV have been reported from more than 30 countries around the globe. At the end of July, monkeypox (MPX) outbreak was even declared a global health emergency by the World Health Organization (WHO). Many aspects remain unclear regarding this outbreak and a deep understanding of orthopoxvirus might have crucial and evident implications. During the era in which people under 45 years old are not protected against VACV, the potential use of orthopoxviruses as a biological weapon raises global concern considering the rapid spreading of the current MPX outbreak in vulnerable populations. Hence, we review the most recent evidence about phylogenesis, pathogenesis, prevention, and treatment for this concerning disease.